Perlindungan Hukum Atas Keterlambatan Pembangunan Apartemen JLS Yang Didasarkan Pada Perjanjian Pemesanan - Patricia Artjan Mylano; Indrati Rini (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research is to find out the form of legal protection for the delay in the construction of the JLS apartment based on the reservation agreement. The type of research method used is the normative juridical method using literature study of legal materials. Marketing is allowed to be carried out before the construction of apartement. There are many legal problems because the building has not reached 20% of the total building so it cannot use PPJB as an authentic deed. So in this case the sale of apartment units through pre-project selling is based on the form of a reservation agreement. In reality, it often harms consumer rights because there are delays in development that cause material and immaterial losses. The Reservation Agreement has fulfilled the legal requirements of the agreement based on Article 1320 of the Civil Code. The delay in the construction of the JLS apartment unit promised by the developer is included as a breach of contract. Legal protection for buyers of these apartments can request reimbursement of costs, losses and interest based on Article 1243 of the Civil Code, Article 7 letter G of the Consumer Protection Law, dispute resolution can be through consensus deliberation efforts, if not reached then dispute resolution can be carried out in public courts or out of court. Keywords: Apartement, Reservation Agreement, breach of contract